Is There a Reformation Into Identity Achievement for Life After Elite Sport? A Journey of Identity Growth Paradox During Liminal Rites and Identity Moratorium - Wendling, Elodie; Sagas, Michael (Frontiers in Psychology, 2021)
Athletes’ identity development upon retirement from elite sport was examined through a model of self-reformation that integrates and builds on the theoretical underpinnings of identity development and liminality while advancing seven propositions and supporting conceptual conjectures using findings from research on athletes’ transition out of sport. As some elite athletes lose a salient athletic identity upon retiring from sport, they experience an identity crisis and enter the transition rites feeling in-between their former athletic identity and future identity post-sport life, during which a temporary identity moratorium status is needed for identity growth. Given the developmental challenges encountered in moratorium and psychosocial processes necessary to establish a new, fulfilling identity for life after elite sport, we identified key conditions, triggers, and processes that advance how a journey of identity growth paradox experienced during liminality serves as a catalyst toward identity achievement. Elite athletes must be encouraged to persevere in this challenging identity search and delay commitments for as long as it is necessary to achieve identity growth despite experiencing uncomfortable feelings of confusion, void, and ambiguity during the liminal phase. Reforming into an achieved identity for life after elite sport would corroborate the successful navigation of transition, as elite athletes evolved into a synthesized sense of self by cementing, through a negotiated adaptation pathway, constructed identity commitments that will provide new beginnings and meaningful directions to their life after elite sport.